Presence 5 for Racial Justice Workshop: Fostering Dialogue Across Medical Education to Disrupt Anti-Black Racism in Clinical Encounters - Megha Shankar; Kelsey Henderson; Raquel Garcia; Gabrielle Li; KeAndrea Titer; Rhonda Graves Acholonu; Utibe R. Essien; Cati Brown-Johnson; Joy Cox; Jonathan G. Shaw; Marie Christine Haverfield; Kenji Taylor; et al. (Association of American Medical Colleges, 2022)
Introduction Anti-Black racism has strong roots in American health care and medical education. While curricula on social determinants of health are increasingly common in medical training, curricula directly addressing anti-Black racism are limited. Existing frameworks like the Presence 5 framework for humanism in medicine can be adapted to develop a novel workshop that promotes anti-racism communication. Methods We performed a literature review of anti-racism collections and categorized anti-racism communication practices using the Presence 5 framework to develop the Presence 5 for Racial Justice Workshop. Implementation included an introductory didactic, a small-group discussion, and a large-group debrief. Participants evaluated the workshop via an online survey, and we analyzed the resulting qualitative feedback. Results A total of 17 participants took part in two workshops, with nine of the participants responding to the evaluation survey. Themes that emerged from survey responses included strengths of and improvements for the workshop structure (protected time for anti-racism discussion, dialogue between learners and faculty) and content (specific phrases and language, practicing self-reflection). Discussion The workshop provides participants with a semistructured discussion around the five anti-racism communication practices. Barriers to implementation include incorporating the workshop into existing curricula and ensuring diverse learners. Barriers to evaluating the workshop include the low survey response rate. Recommendations to improve the workshop include using case-based discussion and varying the workshop structure according to institutional needs. Next steps include an implementation study to evaluate the acceptability, feasibility, and effectiveness of the workshop.